Dark Triad and relational aggression: the mediating role of relative deprivation and hostile attribution bias - Jiang, Yongzhi; Tong, Lifang; Cao, Wenjiao; Wang, Huizhe (Frontiers in Psychology, 2024)
Relational aggression, as a distinct form of aggressive behavior in social relationships, is associated with various physiological and psychological disorders. Although previous research has provided theoretical support for the connection between the Dark Triad (Machiavellianism, psychopathy, and narcissism) and relational aggression, the mediating factors between the two still require in-depth exploration. This study employed a cross-sectional research method to examine the mediating roles of relative deprivation and hostile attribution bias between the Dark Triad and relational aggression. The results indicated that the Dark Triad traits significantly predicted relational aggression. The mediating role of relative deprivation was significant in the relationship between these traits and relational aggression. Hostile attribution bias mediated the relationship between Machiavellianism, psychopathy, and relational aggression, but not between narcissism and relational aggression. Additionally, the serial mediating role of relative deprivation and hostile attribution bias was significant between the Dark Triad traits and relational aggression. This study not only verified the relationship between the Dark Triad and relational aggression but also identified mediating factors providing new useful information for effectively explaining and intervening in malignant interpersonal relationships.